Pregnancy Complications, Correlation With Placental Pathology and Neonatal Outcomes - Loverro, Maria Teresa; Di Naro, Edoardo; Nicolardi, Vittorio; Resta, Leonardo; Mastrolia, Salvatore Andrea; Schettini, Federico; Capozza, Manuela; Loverro, Matteo; Loverro, Giuseppe; Laforgia, Nicola (Frontiers in Clinical Diabetes and Healthcare, 2022)
Purpose We aimed to clarify and contribute to a better comprehension of associations and correlations between placental histological findings, pregnancy evolution, and neonatal outcomes. Study Design This is a longitudinal and prospective observational study, performed between May 2015 and May 2019, on 506 pregnant women. Clinical data related to pregnancy outcome, neonatal health status, and placental histology were primarily collected. Twin pregnancies or malformed newborns were excluded and therefore the study was conducted on 439 cases. These cases have been then subdivided into the following study groups: (a) 282 placentas from pathological pregnancies; and, (b) a control group of 157 pregnancies over 33 weeks of gestational age, defined as physiological or normal pregnancies due to the absence of maternal, fetal, and early neonatal pathologies, most of which had undergone elective cesarean section for maternal or fetal indication. Results A normal placenta was present in 57.5% of normal pregnancies and in 42.5% of pathological pregnancies. In contrast, placental pathology was present in 26.2% of normal pregnancies and 73.8% of pathological pregnancies. Comparison of the neonatal health status with the pregnancy outcome showed that, among the 191 newborns classified as normal, 98 (51.3%) were born from a normal pregnancy, while 93 (48.7%) were born from mothers with a pathological pregnancy. Among the 248 pathological infants, 59 (23.8%) were born from a mother with a normal pregnancy, while 189 (76.2%) were born from pregnancies defined as pathological. Conclusion Placental histology must be better understood in the context of natural history of disease. Retrospective awareness of placental damage is useful in prevention in successive pregnancy, but their early identification in the evolving pregnancy could help in association with biological markers or more sophisticated instruments for early diagnosis.